Corporations in evolving diversity cognition, governance, and institutional rules - Aoki, Masahiko, 1938- (Oxford : Oxford University Press, 2010)
The present global economic crisis demands we look anew at the role of corporations & the working of financial markets around the world. In this book, one of our most eminent economists provides a compelling new analysis of the firm; the role of shareholders, managers & workers; & institutional governance structures.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Corporate governance; Organizational behavior; Organizational effectiveness